(untitled) (Reflection and Critique Law Magazine, 2019)
The motivation for the development of research arose from the perception of the lack of effectiveness of public policies promoted by the Government as a guarantor of the rights of children and adolescents. The objective of the current research is, therefore, to analyze the possibility of judicialization of these public policies, as a way of realizing these rights and greater support to these individuals. The protection of children and adolescents is supported by the legal system, but what is noted is that they are not fully effective, due to several factors that will be pointed out during the development of the study. Thus, the contribution of this study is revealed in the opportunity to know and analyze the possibility of judicialization of public policies with a view to fostering the effectiveness of preventive actions developed by the State aiming at the full protection of children and adolescents prescribed by the Statute of the Child and the Child. Adolescent, pointing out the objectives of public policies and how the state becomes its guarantor. It is further demonstrated that the duty to manage public policies is not only the responsibility of the State, but also of the society that is mostly inert in the ineffectiveness or lack of implementation of the policies created. The research is characterized as being theoretical, qualitative and bibliographic, using the deductive method, drawing on historical, sociological and legal material from books and scientific articles.